MEDIA EDUCATION AND ITS PLACE IN UZBEKISTAN - Yuldashov Sherzod Sattorovich (Web of Journals Publishing, 2025)
The article discusses the generally accepted directions of media education and the media competencies of modern man; the classification of media education; the main variables on which the success of the media education process depends, as well as the social layers on which modern media education is directed. In connection with the increased influence of the media, there is a need to expand the social groups in which media education should be directed.
Keywords: Media education, media and information literacy, media environment, media space, media competence.